The Influence of Emergency Service Management Policies on Response Time and Service Quality at RSUD Bangun Purba, Deli Serdang Regency, in 2026 - Rieska Ariza; Rahmad Gurusinga; Tati Murni Karokaro (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Emergency services represent the frontline of hospital care and require optimal response time and high-quality service delivery, with response time and service quality serving as key performance indicators. The achievement of these indicators is strongly influenced by the implementation of effective emergency service management policies. This study aimed to analyze the effect of emergency service management policies on response time and service quality at Bangun Purba Regional General Hospital, Deli Serdang Regency, in 2025. This study employed a quantitative analytical design, with the study population consisting of patients and/or patients’ families who received services at the Emergency Department of Bangun Purba Regional General Hospital. Data were collected through questionnaires and observation, and analyzed using univariate analysis to describe the distribution of study variables and bivariate analysis to examine the relationships between variables. The univariate analysis indicated that emergency service management policies were generally perceived as moderate to good, while response time performance had not fully met the minimum service standards. Bivariate analysis revealed a statistically significant relationship between emergency service management policies and response time (p < 0.05), as well as between management policies and service quality (p < 0.05). Response time was also significantly associated with service quality (p < 0.05), indicating that faster response time was associated with better perceived service quality. In conclusion, emergency service management policies play a crucial role in improving response time and service quality in the emergency department, highlighting the need for strengthened policy implementation, improved adherence to standard operating procedures, and continuous evaluation to enhance service quality and patient safety.